(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study investigated the multidimensional factors affecting academic achievement in Social Studies among junior secondary school students in Oyo Metropolis, Nigeria, from an educational management perspective. The focus is on student, teacher, school, and home-related variables. A descriptive survey research design was adopted, involving 300 students selected using stratified sampling across ten secondary schools in the study area. Data were collected using a validated questionnaire and analyzed using descriptive statistics (mean, standard deviation) and inferential statistics (ANOVA and post-hoc tests). Findings revealed that student motivation, school administrative support, teacher quality, and parental involvement significantly influence students’ academic performance. Implications for educational managers include the need to strengthen teacher training, improve learning resources, foster school-home collaboration, and introduce student-centered support services.